Sleep initiation patterns and sleep quality among toddlers in the southeast of China: initial study results - Xiaoxia Lin; Xianrui Chen; Yanhui Chen; Ping Xu; Shan Chen (BMC, 2024)
Abstract Background A large number of psychological consequences including sleep health emerged during the 2019 Coronavirus disease (COVID-19) pandemic. Sleep patterns in toddlers are vulnerable to negative environmental exposures, however, very few studies on this topic have been published so far. Objectives In this paper, we aimed to investigate the sleep patterns and associated factors in toddlers from China confined at home in the context of COVID-19 pandemic. Methods From April to November 2021, a convenience sample of 493 parents of young children aged (12-35 months) were surveyed from Fuzhou, Sanming, Quanzhou, Nanping, and Longyan cities in the Fujian Province, China. A cross-sectional survey was conducted via Electronic questionnaires to collect parent and child social-demographic characteristics. The Brief Infant Sleep Questionnaire (BISQ) was used to collect data on sleep practices, sleep duration and patterns, as well as the number of nocturnal awaking . Results The mean age of toddlers was 2.11 years old, and 52.54% (259/493) were males. Among the 493 toddlers' sleep patterns, 331(67.1%) initiated sleep accompanied by parents, 67(13.6%) slept independently, 59 (12.0%) were breast fed/bottle fed to initiate sleep, 27 (5.5%) were held and 9 (1.8%) rocked. The clear longitudinal association between the duration of night-time sleep, the frequency of nighttime awakenings, and various sleep patterns remains clear (p < 0.05). Multiple linear regression analysis indicated that sleep initiation with bottle-feeding/breast-feeding and rocked significantly increased the frequency of nighttime awakenings and reduced the duration of nighttime sleep (p < 0.05), as held was dramatically only for increasing the number of nighttime awakenings (p < 0.05). Multi-variate logistic regression analysis demonstrated that toddlers with severe sleep difficulties had a higher probability of being rocked to initiate sleep (p < 0.05). Conversely, young children with minor sleep problems were more apt to be in bed alone to initiate sleep (p < 0.05). Conclusions During the COVID-19 pandemic, most infants and toddlers initiated sleep accompanied by parents and tend to have electronic media exposure before bedtime. Increased waking at night may be associated with sleep initiation with breast-feeding/bottle-feeding. Therefore, pediatric practitioners in primary community hospitals should pay attention to the education and promotion of sleep hygiene and parenting knowledge of young children to avoid the formation of poor sleep hygiene habits.